Etnoastronomi Perbintangan Masyarakat Lombok - Muhammad Awaludin (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
This research discusses about the ethnoastronomy of the Sasak community on Lombok Island, which analyses knowledge about stars and the movement of celestial bodies in the context of local culture. The Sasak people use certain stars such as Rowot (Pleiades) and Tenggale (Orion) as markers of time and seasons, as well as in the performance of traditional and religious rituals. This study is important to document orally transmitted traditional astronomical knowledge, which contributes to daily life, particularly in agriculture and navigation. This research uses the literature method with a descriptive qualitative approach to reveal the relationship of astronomy to the culture of the Sasak community. The results of the study show that the Sasak people have their own names and functions for the stars in the night sky such as Rowot (Pleiades), Tenggale (Orion), Bintang Basong (Sirius), Bintang Pai (Crux), Bintang Jaran (Pegasus), and Bintang Sok (Scorpion). Among these constellations, two groups of clusters that have an important role in determining time in Lombok community are the Rowot (Pleiades) and Tenggale (Orion) constellations.